Bringing Up Moral Literacy in Primary School Students through the Use of Image Reflection Methods - Akhmad Afroni; Dewi Puspitasari; Ali Burhan; Agnes Widiyaningrum; Noor Malihah; Norman Nofianto; Safitri Yosita Ratri (Edukasia Islamika, 2022)
The increasing moral degradation in Indonesia makes moral education is in high needs. This research is a qualitative research that seeks to find scaffolding strategies applied by teachers in fostering moral literacy among children through the use of image reflection media and finding narratives that are built from children's reflections. Ten elementary school students in Central Java, Indonesia were involved in this study. In collecting data, researchers used semi-structured interviews and observations to strengthen research data. As for analyzing the data, this study uses thematic analysis. Although it has several shortcomings, the research subjects show positive response regarding the use of the image reflection method as an effort to foster moral literacy in early childhood. This method is expected to be an alternative measure in moral teaching, especially at the elementary age level